Kajian Pemanfaatan Susu Nabati Sebagai Pengganti Susu Hewani - Intan Maris; Mohamad Rajih Radiansyah (LPPM Universitas Terbuka, 2021)
In general, milk is a white liquid secreted by animal’s mammary gland and contained lactose.Problems occured when some people have an allergy to lactose thus an alternative is createdin the form of dairy products with plants as the basic ingredient. This study aims to determinethe nutritional value and the advantage of plant-based milk on health and nutrition fulfillmentso it can be used as a substitute of animal milk for people with lactose intolerance. In thisstudy, the milk in plant-based milk refers to extracts of various plants. Plant-based milk has adistinctive odor depending on the plant-based ingredients used. In this article, the study wascarried on the physical characteristics, nutritional values and benefits of plant-based milkconsumption for health and a comparison with animal milk (cow’s milk) was also done. Theliterature indicated that nutritional value of plant-based milk is comparable to animal milk.Despite no observable physical differences between plant-based milk and animal milk, therewas still a need for improvements in the way to add flavour to plant-based milk to attractconsumer’s interest. Plant-based milk has its benefits for heart health due to its lack ofcholesterol levels in it. There are five types of plant-based milk studied within the scope of thisarticle; these are soy, almond, oat, mung beans, and cashew.